Earnings Inequality in Late Nineteenth Century America and Britain - Myeong-Su Yun (Rutgers University, Department of Economics, 2000)
This paper studies the level and the causes of earnings inequality in late nineteenth century America and Britain using microdata from the United States Commissioner of Labor Survey in 1890 and 1891. We examine whether lessons from studies on changes in earnings inequality over time – the importance of skill, especially the skill wage premium, in explaining the changes – can be applied to explaining why America had greater earnings inequality relative to Britain in the late nineteenth century. Using Fields' decomposition methodology, we find that the skill factor is important, albeit not the most important. According to shift share analysis, the differences in earnings inequality between the two countries can be explained mainly by the greater inequality within each skill group.
Keywords: D30; N31; N33; 330; earnings inequality; Fields' decomposition of inequality; late nineteenth century America and Britain; shift share analysis